Harvesting the maximum length of sciatic nerve from adult mice: a step-by-step approach - Bala, Usman; Tan, Kai Leng; Ling, King Hwa; Cheah, Pike See (BioMed Central, 2014)
Background: Over the past several decades, many studies concerning peripheral nerve damage or regeneration have been performed. Mice have been widely used for many of these studies, with the sciatic nerve being the most targeted and preferred nerve. Therefore, techniques for harvesting mouse sciatic nerves of a maximum length that is sufficient for different analyses will be highly valuable. Here we describe a simple step-by-step guide for harvesting the maximum length of mouse sciatic nerve and compare the length of the harvested nerves gathered with the proposed method with nerves obtained using a conventional mid-thigh incision approach. Findings: The sciatic nerve was exposed while holding both hind limbs together in one hand and the tail was gently pulled away in the opposite direction. The nerve was traced by dissecting through its course both distally and proximally and was carefully harvested. The total average length of the sciatic nerves obtained using the proposed harvesting method and the mid-thigh incision method was 22.60 ± 1.62 mm and 7.0 ± 0.76 mm, respectively. This length of harvested nerve allows further dissection into several segments that can be used for additional independent analyses such as histochemical/histological analysis and RNA or protein extraction. Conclusion: The approach described here has several advantages over mid-thigh incision methods in that it: i) allows harvesting of maximum lengths of the sciatic nerve ii) allows simultaneous harvesting of both sciatic nerves, iii) provides time savings; iv) requires no extensive knowledge of veterinary anatomy; and v) provides hassle-free dissection.